1993
DOI: 10.1177/096032719301200505
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Lipid Profile in Rats with Gentamicin-Induced Nephrotoxicity

Abstract: 1 Administration of gentamicin to rats at doses of 20, 40 or 80 mg kg-1 d -1 for 6 days induced nephrotoxicity exhibited by elevated plasma creatinine concentration and a decrease in alkaline phosphatase activity in rat kidney cortex. 2 Gentamicin treatment produced significant elevation in plasma total cholesterol amounting to 70% at the 80 mg kg-1 dose. At this dose, the combined cholesterol fractions of low density and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 15 publications
4
14
0
Order By: Relevance
“…On the other hand, several studies have demonstrated that cisplatin and gentamicin but not amikacin can induce secondary dyslipidemia in the rat (14)(15)(16). In the present study we observed similar hypercholesterolemia and hypertriglyceridemia in the cisplatin-treated rabbits.…”
Section: Discussionsupporting
confidence: 84%
“…On the other hand, several studies have demonstrated that cisplatin and gentamicin but not amikacin can induce secondary dyslipidemia in the rat (14)(15)(16). In the present study we observed similar hypercholesterolemia and hypertriglyceridemia in the cisplatin-treated rabbits.…”
Section: Discussionsupporting
confidence: 84%
“…The antibiotic is known to cause a number of morphological, metabolic and functional alterations [reviewed in 8]. We have recently reported that gentamicin, at the same dose used here, significantly increased plasma triglycerides and decreased plasma phospholipid concentrations [10], Fish oil, on the other hand, is known to be a major source of co-3 fatty acids and alters membrane phos pholipid fatty acid composition and eicosanoid production [11,12]. The protective ef fect is unlikely due to administration of fats per se, as olive oil (which does not contain the said fatty acid) was ineffective in protecting against gentamicin nephrotoxicity.…”
Section: Resultsmentioning
confidence: 74%
“…Sections were examined by light microscopy by a histopathologist unaware of the treatments. Renal histopathological damage (tubular necrosis) was assessed on a score previously described [10] as follows: 0 = no cell necrosis; 1 = mild, usually single cell necrosis in sparse tubules; 2 = moderate, more than one cell involved in sparse tubules; 3 = marked, tubules exhibiting toral necrosis in almost every power field; 4 = massive total necrosis.…”
Section: Methodsmentioning
confidence: 99%
“…Gentamicin binds to membrane phospholipids, alters its function and lead to a condition known as phospholipidosis in humans (De Broe et al, 1984[16]) and experimental animals (Nonclercq et al, 1992[58]). Lysosomal phospholipidosis is caused by: disorder in phosphatidylinositol signaling pathway (Ramsammy et al, 1988[65]), reduced turnover of phospholipids and their accumulation in plasma membrane (Laurent et al, 1982[40]), decrease in the available negative charge for proper function of phospholipases (Mingeot-Leclercq et al, 1995[50]), inhibition of calcium dependent phosphodiesterases (Van Rooijen and Agranoff, 1985[90]) and by inhibition of phospholipases A1, A2 and C1 (Abdel-Gayoum et al, 1993[1]). Phospholipidosis is directly related to toxicity of GM (Kaloyanides, 1992[33]).…”
Section: Tubular Effectsmentioning
confidence: 99%